Synthesis of Palladium Nanodendrites Using a Mixture of Cationic and Anionic Surfactants - Wen, Xin (Langmuir, 2020)
[Image: see text] Surfactants are used widely to control the synthesis of shaped noble-metal nanoparticles. In this work, a mixture of hexadecyltrimethylammonium bromide (CTAB), a cationic surfactant; sodium oleate (NaOL), an anionic surfactant; palladium chloride; and a reducing agent were used in the seed-mediated synthesis of palladium nanoparticles. By controlling the surfactant mixture ratio, we initially discovered that palladium nanodendrites with narrow size distribution were formed instead of the traditional nanocubes, synthesized with only CTAB. In order to investigate the optimal ratio to produce Pd nanodendrites with a high yield and narrow size distribution, samples synthesized with multiple molar ratios of the two surfactants were prepared and studied by transmission electron microscopy, dynamic light scattering, conductance, and ultraviolet–visible spectroscopy. We propose that the addition of NaOL alters the arrangement of surfactants on the Pd seed surface, leading to a new pattern of growth and aggregation. By studying the nanodendrite growth over time, we identified the reduction period of Pd(2+) ions and the formation period of the nanodendrites. Our further experiments, including the replacement of CTAB with hexadecyltrimethylammonium chloride (CTAC) and the replacement of NaOL with sodium stearate, showed that CTA(+) ions in CTAB and OL(–) ions in NaOL play the main roles in the formation of nanodendrites. The formation of palladium nanodendrites was robust and achieved with a range of temperatures, pH and mixing speeds.